1975
DOI: 10.1111/j.1365-2494.1975.tb01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed Production Studies on Perennial Ryegrass, Timothy and Prairie Grass

Abstract: A study over two years involving tiller identification according to month of origin enabled the contribution of individual tillers of perennial ryegrass Grasslands Ruanui, timotby Grasslands Katbu and a local New Zealand strain of prairie grass (Bromus unioloides) to be deternnined at seed barvest. In addition, tbe distribution of seedbeads in different arbitrary emergence groups was detennined so as to allow analysis of individual seedhead components witbin each group.In all species, tillers formed during tb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

1978
1978
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 18 publications
4
31
1
Order By: Relevance
“…0007-0750/78/0900-0205 $02.00 ©1978 Blackwei! Scientific Publications consistently revealed a significant turnover in tiller populations (Langer et al, 1964;Matthews and Westlake, 1969;Hill and Watkin, 1975;Bernard, 1976) and a recurring pattern of high mortality which occurs during each period of active growth. In a seed crop of ryegrass up to 60% of the tillers produced may die prematurely (Spiertz and Ellen, 1972;Hebblethwaite, 1977) and yet the causes of tiller death are not clearly established.…”
Section: Introductionmentioning
confidence: 97%
“…0007-0750/78/0900-0205 $02.00 ©1978 Blackwei! Scientific Publications consistently revealed a significant turnover in tiller populations (Langer et al, 1964;Matthews and Westlake, 1969;Hill and Watkin, 1975;Bernard, 1976) and a recurring pattern of high mortality which occurs during each period of active growth. In a seed crop of ryegrass up to 60% of the tillers produced may die prematurely (Spiertz and Ellen, 1972;Hebblethwaite, 1977) and yet the causes of tiller death are not clearly established.…”
Section: Introductionmentioning
confidence: 97%
“…Grazing reduces the allocation to reproductive structures by removing rudimentary inflorescences or reducing photosynthetic surfaces and, consequently, the ability to photosynthesize (Hill and Watkin 1975, Caldwell et al 1981, Butler and Briske 1988. On the other hand, grazing can increase the allocation to reproductive organs through its influence on tiller density and age-class distribution (Deregibus et al 1985, Butler and Briske 1988, Noy-Meir and Briske 1996.…”
Section: Introductionmentioning
confidence: 99%
“…It would appear that the increased proportion of tillers in the older categories in the S treatment populations caused a shift towards earlier flowering. It has long been known that the oldest tillers within the tiller population of a grass sward contribute the largest proportion of flowering tiller (Langer & Lambert, 1959;Hill & Watkin, 1975). Hill & Watkin (1975) also demonstrated that management, in their case grazing v. no grazing, can cause a shift towards higher numbers of early-emerging flower heads, but this is the first study to demonstrate long-term effects of spring grazing management on flowering in the following year.…”
Section: Long-term Effectsmentioning
confidence: 95%
“…It has long been known that the oldest tillers within the tiller population of a grass sward contribute the largest proportion of flowering tiller (Langer & Lambert, 1959;Hill & Watkin, 1975). Hill & Watkin (1975) also demonstrated that management, in their case grazing v. no grazing, can cause a shift towards higher numbers of early-emerging flower heads, but this is the first study to demonstrate long-term effects of spring grazing management on flowering in the following year. The earlier flowering of the S treatment swards would also have resulted in an earlier decline in the digestibility of the crop as the inflorescences matured (Spedding & Diekmahns, 1972).…”
Section: Long-term Effectsmentioning
confidence: 95%